Development and application of fish cell lines: a review - SAHUL HAMEED, A S (The Indian Journal of Animal Sciences, 2010)
Cell culture has become one of the major tools used in the life sciences today. Tissue Culture is the general term for the removal of cells, tissues, or organs from an animal or plant and their subsequent placement into an artificial environment conducive to growth. This environment usually consists of a suitable glass or plastic culture vessel containing a liquid or semisolid medium that supplies the nutrients essential for survival and growth. The culture of whole organs or intact organ fragments with the intent of studying their continued function or development is called Organ Culture. When the cells are removed from the organ fragments prior to, or during cultivation, thus disrupting their normal relationships with neighboring cells, it is called Cell Culture. In this paper, development and application of fish cell lines are discussed.